New Technologies in Surgical Oncology - Mussa, Antonio; SpringerLink (Online service) (Milano : Springer Milan, 2010)
Oncological surgeons are often requested in their clinical practice to identify and manage uncommon and complex situations. It is therefore of the utmost importance that they are well aware of the most recent technological evolutions, in order to achieve the best possible results in term of oncological outcome, with a concern on quality of life and economical issues. Furthermore, new techniques can give a fundamental contribution in overcoming the limitations of standard approaches. An essential aim of this book is to underline the great importance and the need of an effective coordination of multi-disciplinary care among surgeons, medical oncologists, radiation therapists, plastic surgeons and ancillary services, in order to optimise patient outcome.
The Evolution of Surgical Oncology -- Minimally Invasive Techniques in Surgical Oncology -- Radioguided Surgery in Oncological Surgery -- Prosthetic Materials in Surgical Oncology -- Intraoperative Radiotherapy -- New Technologies in Oncological Endocrine Surgery -- Robots in Oncological Surgery -- Endoscopy and Surgical Oncology -- Senologic Oncology and Reconstructive Surgery -- Transplants in Surgical Oncology -- Locoregional Therapies and Surgical Oncology -- Hemostatic Agents in Surgical Oncology -- Palliative Techniques and Supportive Procedures in Surgical Oncology -- Ethical Aspects in Surgical Oncology.
Keywords: Medicine; Interventional radiology; Nuclear medicine; Oncology; Cancer -- Surgery; Abdomen -- Surgery; Endoscopic surgery; Medicine & Public Health; Surgical Oncology; Abdominal Surgery; Minimally Invasive Surgery; Oncology; Interventional Radiology; Nuclear Medicine